STUDI DESKRIPTIF IMPLIKASI PEMBELAJARAN TEMATIK BERBASIS HADIS AKHLAK PADA SANTRI DINIYAH TAKMILIYAH AL-IKHLAS LEUWIGAJAH - Ridlo, Muhammad Abdurrasyid; Qurratal Jamilah, Asyfiya; Fitriani (Akademika : Jurnal Keagamaan dan Pendidikan, 2024)
The identified problem is the need for an educational approach that aligns character development with Islamic understanding. This study aims to identify the implications of thematic based learning on Hadith Akhlaq for students of Diniyah Takmiliyah at Al-Ikhlas Leuwigajah. The research methodology used is qualitative descriptive, employing data collection techniques through participatory observation and in-depth interviews. Findings indicate that thematic based learning on Hadith Akhlaq positively contributes to the moral and spiritual character development of students, enhances their understanding of religious teachings, and strengthens the relationship between religious knowledge and daily life.